Pilotski projekt Obnova katastra na območju Bakarskega zaliva - Fiedler, Teodor (Geodetski vestnik, 1997)
The results of the work on the Bakar Bay pilot project are described in the paper. Testing was performed with the aim of modernizing data acquisition for cadastral surveys as the geometric basis of LIS to be used exclusively for registering indispensable attributes connected with real estate. The concept of a rather simplified database was suggested with a maximally simplified geometry connected with the base through plot numbers.
Keywords: geodezija; projekti; zemljiški kataster